1988
DOI: 10.1159/000293712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tinidazole Given as a Single Dose and on 2 Consecutive Days for the Treatment of Nonspecific Bacterial Vaginosis

Abstract: Nonspecific bacterial vaginosis, defined as the presence of clue cells, was treated in a randomized, double-blind study with (1) tinidazole 2g as a single dose (82 patients), (2) tinidazole 2 g on 2 consecutive days (84 patients), and (3) with placebo (81 patients). The cure rates, both clue cells and Gardnerella vaginalis absent, were 51, 74 and 4%, respectively. A closer clinical and microbiological evaluation showed the 2-day regimen to be superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Trials evaluating oral regimens of 1–2 g daily for 1–5 days have given favorable results 30. Tinidazole was licensed recently in the US for the treatment of BV 31…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…Trials evaluating oral regimens of 1–2 g daily for 1–5 days have given favorable results 30. Tinidazole was licensed recently in the US for the treatment of BV 31…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…In both the reports comparing a single 2g dose of tinidazole to a single 2g dose of metronidazole, tinidazole produced higher efficacy rates. A report by Ekgren13 which compared a single 2g dose of tinidazole to a 2g × 2 day dose of tinidazole demonstrated higher efficacy with the 2 day dosing regimen. In that randomized, double-blind study report the 2 day dose produced an efficacy rate of 74% vs. 51% efficacy for the single 2g dose with only a small increase in the reported side effects (44% vs. 39%).…”
Section: Discussionmentioning
confidence: 99%
“…It is better tolerated than metronidazole 25,26 and very cheap (wholesale price per 2 g dose ≈ US$ 0.07). Studies of singlemdose tinidazole in women with BV have shown a wide range of effectiveness (51-97%) [27][28][29][30] but used different definitions of BV and cure. Experts now agree that the goal of BV treatment is symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%